Sequencing Crop Genomes: A Gateway to Improve Tropical Agriculture - Gincy Paily Thottathil; Kandakumar Jayasekaran; Ahmad Sofiman Othman (Tropical Life Sciences Research, 2016)
Agricultural development in the tropics lags behind development in the temperate latitudes due to the lack of advanced technology, and various biotic and abiotic factors. To cope with the increasing demand for food and other plant-based products, improved crop varieties have to be developed. To breed improved varieties, a better understanding of crop genetics is necessary. With the advent of next-generation DNA sequencing technologies, many important crop genomes have been sequenced. Primary importance has been given to food crops, including cereals, tuber crops, vegetables, and fruits. The DNA sequence information is extremely valuable for identifying key genes controlling important agronomic traits and for identifying genetic variability among the cultivars. However, massive DNA re-sequencing and gene expression studies have to be performed to substantially improve our understanding of crop genetics. Application of the knowledge obtained from the genomes, transcriptomes, expression studies, and epigenetic studies would enable the development of improved varieties and may lead to a second green revolution. The applications of next generation DNA sequencing technologies in crop improvement, its limitations, future prospects, and the features of important crop genome projects are reviewed herein. Perkembangan agrikultur di tropika ketinggalan di belakang perkembangan di kawasan temperat disebabkan kekurangan teknologi maju dan pelbagai faktor biotik dan abiotik. Untuk menghadapi permintaan yang meningkat terhadap makanan dan lain-lain produk berteraskan tumbuhan, varieti tanaman yang lebih baik perlu dihasilkan. Untuk membiak varieti yang lebih baik ini, pemahaman yang baik tentang genetik tanaman diperlukan. Dengan adanya teknologi penjujukan DNA generasi terkehadapan, banyak genom tanaman telah dijujuk. Kepentingan utama diberikan kepada tanaman makanan termasuk bijirin, tanaman ubi, sayuran, dan buahan. Maklumat jujukan DNA amat penting untuk mengenal pasti gen utama yang mengawal ciri agronomi penting dan untuk menentukan kevariabelan genetik antara kultivar. Namun, penjujukan semula DNA secara besar-besaran serta kajian pengekspresan gen perlu dilakukan untuk meningkatkan dengan ketara pemahaman kita dalam genetik tanaman. Aplikasi pengetahuan dari genom, transkriptom, kajian pengekspresan gen, dan epigenetik akan membolehkan perkembangan varieti yang lebih baik dan mungkin mengarah kepada revolusi hijau kedua. Aplikasi teknologi penjujukan DNA generasi terkehadapan dalam menambah baik tanaman, limitasinya, prospek masa hadapan, dan ciri-ciri penting projek genom tanaman diulas di sini.